Economic effect evaluation and collaborative development path research of Linyi red tourism - Gong, Ling (Pacific International Journal, 2024)
Linyi is rich in red tourism resources, with high quality, strong attraction, and great development potential. In recent years, the red tourism industry in Linyi has achieved significant development. Using econometric analysis models, using the Linyi red tourism development (measured by domestic income of red tourism) and regional economic growth (measured by GDP) from 2000 to 2019 as endogenous variables, a VAR model is constructed to empirically analyze the impact of red tourism development on regional economic growth. Through research, it has been found that a positive impact on the domestic and international income growth rates of Linyi’s red tourism has a positive impact on the GDP growth rate, and from a trend perspective, the duration is relatively long; This indicates that the domestic and international income of Linyi’s red tourism has a significant promoting effect on Linyi’s economic growth. From the results of variance decomposition, it can be seen that the contribution rates of domestic and international income from Linyi’s red tourism to Linyi’s economic growth are not significant at first, without considering the contribution rate of Linyi’s economic growth itself. However, there has been a significant growth trend since the second period. Based on the analysis of the economic effects of red tourism, considering the overall nature of Linyi’s red culture, proximity to geographical location, convenient transportation, and government support, this paper analyzes the specific path for the coordinated development of Linyi’s red tourism. Construct a top-level design for the coordinated development of red tourism resources from the perspectives of goal coordination, organization and interest coordination, and institutional coordination.